High lifetime probability of screen-detected cervical abnormalities. (December 2017) - Pankakoski, Maiju; Heinävaara, Sirpa; Sarkeala, Tytti; Anttila, Ahti
Objective: Regular screening and follow-up is an important key to cervical cancer prevention; however, screening inevitably detects mild or borderline abnormalities that would never progress to a more severe stage. We analysed the cumulative probability and recurrence of cervical abnormalities in the Finnish organized screening programme during a 22-year follow-up. Methods: Screening histories were collected for 364, 487 women born between 1950 and 1965. Data consisted of 1 207, 017 routine screens and 88, 143 follow-up screens between 1991 and 2012. Probabilities of cervical abnormalities by age were estimated using logistic regression and generalized estimating equations methodology. Results: The probability of experiencing any abnormality at least once at ages 30–64 was 34.0% (95% confidence interval [CI]: 33.3–34.6%) . Probability was 5.4% (95% CI: 5.0–5.8%) for results warranting referral and 2.2% (95% CI: 2.0–2.4%) for results with histologically confirmed findings. Previous occurrences were associated with an increased risk of detecting new ones, specifically in older women. Conclusion: A considerable proportion of women experience at least one abnormal screening result during their lifetime, and yet very few eventually develop an actual precancerous lesion. Re-evaluation of diagnostic criteria concerning mild abnormalities might improve the balance of harms and benefits of screening. Special monitoring of women with recurrent abnormalities especially at older ages may also be needed.